Analisis Pengaruh Indeks Pendidikan Terhadap Tingkat Pengangguran Terbuka di Provinsi Jawa Barat Periode 2018-2021 - Ucu, Ucu; Alifia, Rinandita Malika; Syafaat, Agustin Aura; Nabila, Finkan; Ulummuddin, Ihya; Desmawan, Deris (Universitas Labuhanbatu, 2024)
This study aims to see how the impact of the education index is on the open unemployment rate from 2018 to 2021 (a case study in West Java Province). The variables studied in this study are the level of open unemployment as the dependent variable, the level of education as the independent variable. The research method used is a quantitative method using secondary data from a reliable source, namely the Central Bureau of Statistics (BPS). Multiple linear regression analysis method. The results showed that partially the education variable had a positive and significant impact on the unemployment index. Where if there is an increase in the level of education then the unemployment rate will also increase. This proves that there is a unidirectional correlation between the level of education and the level of unemployment.